Zzass cendols / Nur Syahirah Omar ... [et al.] - Omar, Nur Syahirah; Suhami, Nur Zahirah; Fauzi, Nor Anisah; Hasan, Nurul Syaliza; Mohd Mokhtar, Nurul Zahira Imani; Mahdzar, Mazlina (Universiti Teknologi MARA, Kedah, 2023)
Products and services provided by Cendols are rapidly gaining recognition as traditional cuisine in Malaysia. Cendols was founded in the 19th century. The food and beverage industry will be held to a higher standard as a result of this. Cendols has the potential to become a household brand across the nation, being linked not just with outstanding product quality but also with worldwide best practices. We provide customers with Cendol Zzass, a product that includes drinks that may be consumed at any time and in any location. Our goal is to spread awareness about sustainable products among the general public in the hopes of persuading them to purchase items that are better for the environment, while at the same time preserving their capacity to take pleasure in using such items. In the meantime, we implement the use of IT by using QR code for the customer to choose the flavor to their liking and giving feedback of the Cendol and the packaging. Therefore, the originality of the product is connected to the goals of the inventor, which include making the product as user-friendly as possible for the general public in order to make a positive contribution to the net profit of the regional economy. In addition, the suggested product's usefulness is that it has the potential to provide people not only in the local area but also in other countries the pleasure of being the first to experience the product's flavor. In conclusion, the findings and the conversation are used in order to enhance and simplify the process involved in the production of the product while simultaneously making it more pleasurable for everyone involved.